MENSURATION OF THE QUALITY OF THE PHONE SERVICE, USING PROBABILISTIC SAMPLING - Ramos Ramírez, Julio (2005)
The present article tries about the statistical methodology implemented for the supervision of the installation for phone fines, by means of the calculation of an established parameter inside the supervision procedures that measures the grade of execution of the service offered by the concessionary company.